Inefficacy of self-regulation of alcohol advertisements: a systematic review of the literature - Vendrame, Alan; Pinsky, Ilana (Revista brasileira de psiquiatria, 2011)
The most recent scientific literature indicates that alcohol advertising influences behavior, particularly early and higher alcohol consumption by children and adolescents. From a public health perspective, alcohol advertising should be restricted. In many countries, as well as in Brazil, limits to alcohol advertising are established by industry self-regulation (e.g. controlled by the advertising community itself). We examined in this review all articles on the subject of industry self-regulation of alcohol advertising published in the international literature. A systematic literature review was conducted on articles investigating the effectiveness of self-regulation of alcohol advertisings. The search was conducted in Medline, SciELO, Camy and Google Scholar, between the years of 1991 and 2010. In addition, the "snowball" technique for the indication of the main authors on the subject was employed. From the articles found, 11 focused on the subject discussed here. The set of articles obtained indicates that industry self-regulation of alcohol advertising does not show evidence of efficacy. In other words, such a regulation does not prevent, for instance, alcohol advertising directed at children and adolescents. Further measures should be considered for the control and the broadcast of alcohol advertising, such as independent monitoring, legal control.